Let's look at animal bottoms - Perkins, Wendy, 1957- (Mankato, Minn. : Capstone Press, 2007)
"Simple text and photographs present a variety of animal bottoms and their uses"--Provided by publisher.
Bottoms at work -- Kinds of bottoms -- Awesome bottoms -- Glossary -- Read more -- Internet sites -- Index.
Includes bibliographical references (p. 23) and index.
"RL: 1; IL: PreK-2"--P. [4] of cover.
Keywords: Buttocks -- Juvenile literature; Buttocks